Comparison of Supraclavicular Oblique Incision With Traditional Low Collar Incision Approach for Thyroidectomy in Differentiated Thyroid Cancer - Jiang, Bo; Qu, Cheng; Jiang, Chaoyu; Zhang, Chen; Shen, Song; Luo, Yuqian; Su, Lei (Frontiers in Oncology, 2022)
Background Various incisions and approaches for thyroidectomy have been developed to treat differentiated thyroid cancer (DTC). Supraclavicular oblique incision (SOI) thyroidectomy (SOIT) has been applied in DTC patients over the past ten years. However, the safety and efficacy of this approach were yet to be confirmed. Aim This study aimed to compare the surgical and patient-related outcomes between SOIT and traditional low collar incision thyroidectomy (TLCIT) in patients with DTC. Methods We retrospectively screened all patients with DTC who received thyroid lobectomy from October 2020 to October 2021. The surgical results and patient-related outcomes assessed at 1 and 6 months after surgery by questionnaire were compared between the SOIT and TLCIT groups. Results A total of 128 patients were included in this study, of whom 38 patients (30.5%) were operated on with SOIT and 89 patients (69.5%) with TLCIT. There was no significant difference in demographic characteristics and thyroid features between the two groups. Despite comparable operative time (61.9 ± 12.1 vs. 59.9 ± 15.0 min, p = 0.425), the SOIT group had a smaller neck incision (4.4 ± 0.7 vs. 5.0 ± 1.0 cm, p = 0.002), a shorter duration of postoperative drainage (2.4 ± 0.5 vs. 2.7 ± 0.9 days, p = 0.019), less volume of postoperative drainage (48.4 ± 24.6 vs. 60.3 ± 22.8 ml, p = 0.040), and shorter postoperative hospitalization (3.2 ± 0.5 vs. 3.6 ± 0.9 days p = 0.006), as compared with the TLCIT group. At 1-month follow-up after surgery, SOIT showed better performance in preventing hypoparathyroidism (p = 0.026) and abnormal neck sensation (p = 0.010) and in improving cosmetic satisfaction (p = 0.036) than TLCIT. At 6-month follow-up, SOIT was feedback with better cosmetic satisfaction (p < 0.001) and a lower percent of abnormal neck sensation (p = 0.031) or movement (p = 0.005). Conclusion Our study suggests that minimally invasive surgery using the SOI provides superior surgical and patient-related outcomes compared with surgery using a traditional low collar incision (TLCI) in patients with DTC.